Effect of cultivar on sensory characteristics, chemical composition, and nutritional value of stoned green table olives - Malheiro, Ricardo (2013)
The effect of olive cultivar on sensory characteristics, chemical composition, and nutritional value of traditional stoned green table olives “alcaparras” was studied. The most representative cultivars from Trás-os-Montes region, Portugal (Cv. Cobrançosa, Madural, Negrinha de Freixo, Santulhana, and Verdeal Transmontana) were studied. The results showed that, regardless the cultivar, water was the main constituent with values greater than 70%, followed by fat that varied between 12.5% and 20.1%. Carbohydrates amount was greater in Cv. Madural (9.2%) and those produced from Cv. Cobrançosa had higher level of nitrogenous compounds, with 1.4%. Ashes contents of table olives varied from 1.6% to 1.9%, without significant differences among cultivars. Moreover, 100 g of “alcaparras” provided an energetic value between 154 and 212 kcal for Cv. Madural and Verdeal Transmontana, respectively. Oleic acid was the main fatty acid detected (higher than 66.9%), followed by palmitic acid (10.8–13.3%) and linoleic acid (2.7–10.3%). A linear discriminant model was established based on the “alcaparras” table olives fatty acids profile. Three fatty acids (C16:0, C18:0, and C18:3) and total saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids contents allowed distinguishing between the five olive cultivars studied, with overall sensitivity and specificity of 100%. The total content of vitamin E of the table olives varied from 3.5 and 6.0 mg/kg (for Cv. Santulhana and Negrinha de Freixo, respectively), being α-tocopherol the most abundant. The consumer’s panel showed higher preference for the table olives of Cv. Verdeal Transmontana and Negrinha de Freixo, while Cv. Madural was negatively characterized in all the descriptors evaluated. Keywords Olea europaea L. . Stoned table olives.